1983
DOI: 10.1007/bf02534707
|View full text |Cite
|
Sign up to set email alerts
|

Increases in hyperlipoproteinemia, disturbances in cholesterol metabolism and atherosclerosis induced by dietary restriction in rabbits fed a cholesterol‐rich diet

Abstract: The influence of dietary restriction on cholesterol transport and metabolism was investigated in rabbits given standard or cholesterol-rich diets (0.2 g cholesterol/kg body weight daily) either ad libitum or with 50% caloric ration. Dietary restriction which has only a slight influence in control rabbits markedly aggravated the disturbances induced by exogenous cholesterol. With limited feeding, control rabbits presented a moderate increase in plasma cholesterol, whereas marked aggravation of hypercholesterole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 39 publications
3
7
0
Order By: Relevance
“…Interestingly, total serum cholesterol increased dramatically in the diet group compared with the other 2 groups. Although dietary restriction and weight loss in humans typically leads to a reduction in serum cholesterol, it has been reported that diet-restricted, cholesterol-fed NZW rabbits exhibit hypercholesterolemia, including elevations in LDL and VLDL cholesterol (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, total serum cholesterol increased dramatically in the diet group compared with the other 2 groups. Although dietary restriction and weight loss in humans typically leads to a reduction in serum cholesterol, it has been reported that diet-restricted, cholesterol-fed NZW rabbits exhibit hypercholesterolemia, including elevations in LDL and VLDL cholesterol (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Reitman et al (1982) found plasma cholesterol concentrations in excess of 700 mg/dl when miniature swine were fed diets containing 15% beef tallow and 1.5% cholesterol. In our study, diets that contained less than 0.1% cholesterol (equivalent to a daily intake of approximately 2500 mg in a 70 kg man) produced small but significant increases in plasma cholesterol concentrations in both beef-and soy-fed pigs (Table 7) Liepa et al, 1980;Lacombe et al, 1983), but the effects of restriction vary with species and with length and degree of restriction.…”
Section: Discussionmentioning
confidence: 46%
“…Lacombe et al (1983) further demonstrated that the cholesterol content of the diet influences the effects of caloric restriction on cholesterol metabolism. In the study by Lacombe et al (1983), rabbits fed a cholesterol-free diet at 50% of ad libitum intake had only moderate increases in plasma cholesterol, while restricted-fed rabbits receiving a cholesterol-rich diet had marked hypercholesterolemia and a greater degree of atherosclerosis.…”
Section: Effects Of Dietary Restriction On Cholesterol Metabolismmentioning
confidence: 96%
See 2 more Smart Citations